2020
DOI: 10.1007/978-3-319-37076-7_66-1
|View full text |Cite
|
Sign up to set email alerts
|

Basics of Self-Regeneration

Abstract: Regeneration is a fascinating phenomenon spanning several levels of complexity, allowing organisms to repair, renew, and reconstitute missing or damaged parts. Despite significant efforts to understand regeneration, the lack of adequate technology has slowed advances in the field until very recently. Since the beginning of the eighteenth century, scientists have looked toward animal models while striving to dissect the cellular and molecular pathways that drive regeneration. Although we are still far from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 219 publications
(293 reference statements)
0
2
0
Order By: Relevance
“…GO analysis showed that, in both cases, there was an enrichment in genes related to processes of cell migration, cell adhesion, ECM disassembly and ECM organization (Fig. 3F, Table S4), all of which previously associated with the formation of a blastema (reviewed in Aires et al, 2020).…”
Section: Transcriptomic Analysis Of Mandible Regeneration After Later...mentioning
confidence: 79%
“…GO analysis showed that, in both cases, there was an enrichment in genes related to processes of cell migration, cell adhesion, ECM disassembly and ECM organization (Fig. 3F, Table S4), all of which previously associated with the formation of a blastema (reviewed in Aires et al, 2020).…”
Section: Transcriptomic Analysis Of Mandible Regeneration After Later...mentioning
confidence: 79%
“…Appendage regeneration has fascinated biologists for centuries, 1 as uncovering the molecular and cellular players regulating this process holds potential for therapies aimed at regenerating human limbs. While there are many different model organisms (e.g.…”
Section: Introductionmentioning
confidence: 99%